Clinical efficacy of intra-articular infusion of cocktail combined with tranexamic acid in the treatment of middle-age and older patients with frozen shoulder following arthroscopic capsular release - Bai, Xiaojin; Bai, Fan; Wang, Zhi; Zhang, Yan; Liu, Fuying; Wang, Qibing (Frontiers in Surgery, 2023)
Objective: To investigate the clinical efficacy of arthroscopic capsular release and postoperative intra-articular infusion of cocktail combined with tranexamic acid (TXA) in the treatment of patients with frozen shoulder. Method: A total of 85 middle-aged and older patients with frozen shoulder who underwent arthroscopic capsular release and received intra-articular infusion of TXA alone (n = 28), cocktail alone (n = 26), and cocktail plus TXA (n = 31) after surgery were retrospective analyzed. The drainage volume within 24 hours after surgery, postoperative length of hospital stay, postoperative complications, visual analog scale (VAS), Neer shoulder assessment scale, ASES score, and range of motion (ROM) of the shoulder joint at 1 day, 1 week, 1 month, and 3 months after surgery in all three groups were recorded and compared. Results: Postoperative length of hospital stay was significantly shorter in the cocktail + TXA and cocktail groups than that in the TXA group. Postoperative drainage volume was significantly higher in the cocktail group compared with TXA + cocktail group (P<0.05). At 1 day and 1 week after surgery, pain was more pronounced in the TXA group, which was significantly relieved in the cocktail and the cocktail + TXA groups (P<0.05). Pain was significantly relieved in all the three groups at 1 and 3 months after surgery. Significant functional improvement of the shoulder was achieved in all three groups at 1 week after surgery, the improvement was apparent in the cocktail + TXA groups (P<0.05), followed by the cocktail group. At 1 month after surgery, patients in the cocktail + TXA groups obtained excellent functional recovery of the shoulder joint. At 3 months after surgery, patients in all the three groups both obtained good recovery of the shoulder joint function, and the recovery was apparent in the cocktail + TXA groups (P<0.05). Conclusion: Arthroscopic capsular release and postoperative intra-articular infusion of cocktail combined with TXA has good safety and efficacy in the treatment of middle-age and older patients with frozen shoulder, which can reduce postoperative pain and intra-articular bleeding, promote early postoperative functional exercises and accelerate early postoperative recovery.